Neuromuscular control deficits and the risk of subsequent injury after a concussion: A scoping review - Howell, D. R.; Lynall, R. C.; Buckley, T. A.; Herman, D. C. (Sports Medicine, 2018)
An emerging area of research has identified that an increased risk of musculoskeletal injury may exist upon returning to sports after a sport-related concussion. The mechanisms underlying this recently discovered phenomenon, however, remain unknown. One theorized reason for this increased injury risk includes residual neuromuscular control deficits that remain impaired despite clinical recovery. Thus, the objectives of this review were: (1) to summarize the literature examining the relationship between concussion and risk of subsequent injury and (2) to summarize the literature for one mechanism with a theorized association with this increased injury risk, i.e., neuromuscular control deficits observed during gait after concussion under dual-task conditions. Two separate reviews were conducted consistent with both specified objectives. Studies published before 9 December, 2016 were identified using PubMed, Web of Science, and Academic Search Premier (EBSCOhost). Inclusion for the objective 1 search included dependent variables of quantitative measurements of musculoskeletal injury after concussion. Inclusion criteria for the objective 2 search included dependent variables pertaining to gait, dynamic balance control, and dual-task function. A total of 32 studies were included in the two reviews (objective 1 n = 10, objective 2 n = 22). According to a variety of study designs, athletes appear to have an increased risk of sustaining a musculoskeletal injury following a concussion. Furthermore, dual-task neuromuscular control deficits may continue to exist after patients report resolution of concussion symptoms, or perform normally on other clinical concussion tests. Therefore, musculoskeletal injury risk appears to increase following a concussion and persistent motor system and attentional deficits also seem to exist after a concussion. While not yet experimentally tested, these motor system and attentional deficits may contribute to the risk of sustaining a musculoskeletal injury upon returning to full athletic participation.